Synthesis and Characterization of Zinc(II) Complex of Schiff Base of Cefadroxil - Thirumagal, B.; Malik, Suman (Asian Journal of Chemistry, 2010)
Zinc(II) complex with Schiff base of cefadroxil (salicylidene cefadroxil) of the type ZnL2, (L = deprotonated Schiff base of cefadroxil) have been prepared. The Schiff base obtained by the condensation of cefadroxil with salicylaldehyde. They form 2:1 ligand to metal complexes with Zn(II) as indicated by conductometric titrations. The general structure assigned to these complexes is supported by mass, UV, IR spectral bands.